2011
DOI: 10.1088/0004-637x/737/1/14
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Experiments on Fine Structure Within Reconnecting Current Sheets in Solar Flares

Abstract: We perform resistive magnetohydrodynamic simulations to study the internal structure of current sheets that form during solar eruptions. The simulations start with a vertical current sheet in mechanical and thermal equilibrium that separates two regions of the magnetic field with opposite polarity which are line-tied at the lower boundary representing the photosphere. Reconnection commences gradually due to an initially imposed perturbation, but becomes faster when plasmoids form and produce small-scale struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
147
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(171 citation statements)
references
References 60 publications
19
147
2
3
Order By: Relevance
“…They concluded that the difference in velocities of plasma blobs could be ascribed to the reconnection processes occurring in the different environments. Similar phenomenon was also observed in numerical experiments on the reconnection process taking place in two-ribbon flares (see also Forbes and Malherbe 1991;Riley et al 2007;Shen et al 2011).…”
Section: Upward Reconnection Outflowssupporting
confidence: 82%
See 4 more Smart Citations
“…They concluded that the difference in velocities of plasma blobs could be ascribed to the reconnection processes occurring in the different environments. Similar phenomenon was also observed in numerical experiments on the reconnection process taking place in two-ribbon flares (see also Forbes and Malherbe 1991;Riley et al 2007;Shen et al 2011).…”
Section: Upward Reconnection Outflowssupporting
confidence: 82%
“…Panels in Fig. 12 display LASCO C2 images of the same process that had been enhanced by the wavelet technique, which further indicates that discriminating a post-CME CS from a streamer CS is not difficult, although in both cases the tearing mode instability could take place in the same fashion (e.g., see also Einaudi et al 2001) since the occurrence of the tearing mode depends on the length to thickness ratio of the CS (e.g., see Furth et al 1963;Loureiro et al 2007;Ni et al 2010;Shen et al 2011;Bárta et al 2011aBárta et al , 2011bMei et al 2012) no matter whether the CS is stretched by the expanding solar wind, or by the disrupting coronal magnetic field.…”
Section: Upward Reconnection Outflowsmentioning
confidence: 96%
See 3 more Smart Citations